Research of the corporal composition and the physical aptitude in students from first cycle of Union Peruvian University, Tarapoto, 2012 - Salinas, Saulo (2013)
In the last ages cancer became the mortal number one illness in global scale, nowadays is the obesity, which presents without any distinction of age, gender, socioeconomic level neither religion. The target of the study was to describe the corporal composition and the physical aptitude associated to health of students of Union Peruvian College – Tarapoto. The sample of the study was conformed of 318 students, both genders, between the ages from 16 to 19. The research design is no experimental descriptive. In corporal composition we obtained the (BMI) body mass index and to describe the physical aptitude associated to health we take five tests: mile race, push up, trunk lift, 30 seconds abdominal, and 30 seconds Burpee. The results show that when we evaluate the BMI in the students, we obtained a 54.72% underneath the right weight, 26.73% in the right weight and an 18.55% finds between pre obese and extremely obese. The average values in males of 16 and 19 in the sum of three folds were 38.8% and 36.9%, unlike the average values displayed by female gender; however, males between 17 and 18 show the 38.5% and 36.6% indicating that they increased their average values in contrast to females. Also, in the physical aptitude test, in both genders, there is a significant increase of the average values in favor of males, except in the mile race test when, at the age of 19, females get lower performance.